Exploring the issue of teacher burnout in Malaysian educational settings - Thomas, Nur Sakinah; Ahmad, Nor Aniza; Mohd Fakhruddin, Fathiyah (Association for Researcher of Skills and Vocational Training, 2024)
In recent years, the issue of teacher burnout has become critical as many studies have reported its global rising cases. Although the studies provide coping strategies, management techniques and burnout scores, the implementation needs to be more specific and practical for diverse cases. Moreover, measuring the levels and identifying the causes will not resolve the problem, so it is crucial to address this issue urgently as it is now affecting teachers’ mental health. However, the direction to address this issue is still unclear as cases are still rising. Therefore, this study aims to explore the issue of teacher burnout by narrowing the focus to Malaysia to discover a clearer direction to initiate effective interventions in managing and preventing teacher burnout. This study employs a narrative review method to analyse, synthesise, and evaluate critically some selected papers related to teacher burnout they affect teachers and the educational settings. It reveals the urgency to address the issue which is increasing and affecting teachers’ emotional and mental wellbeing while causing teacher attrition. It also uncovers the insights of the issue to inspire burnout teachers, bring awareness of the urgency and the dire need to manage their burnout and improve their wellbeing as a catalyst to sustain in their teaching profession. Eventually, it supports the Malaysian Ministry of Education's initiative to empower teacher wellbeing and the National Philosophy of Education to attain personal wellbeing. Hence, it contributes to the efforts to prevent teacher burnout by revealing the highlighted symptoms and factors of teacher burnout and promoting the significance of teacher wellbeing for a sustainable effective education.